Contemporary Microeconomic Foundations for the Structure and Management of the Public Sector - Lewis Evans; Graeme Guthrie; Neil Quigley (New Zealand Government, The Treasury, 2012)
The new public management of the 1980s was based in part on a range of important new insights about the role of transaction and agency costs arising from contractual incompleteness in defining the boundaries of the firm and the governance relationships within it. In this paper, we consider the literature of the last 25 years which extends our understanding of allocations of ownership rights and the boundaries of the firm as responses to contractual incompleteness. From this perspective, ownership represents an allocation of control rights to those with the potential to make the most important (value-enhancing) relationship-specific investments. We provide an outline of this modern approach to contractual incompleteness, illustrate its application to a range of issues in public and private ownership, investment, governance and decision-making, and provide suggestions about the impact that this approach might have on the scope, structure and management of the public sector in the 21st century.
Keywords: H40; L20; L33; G31; 330; Incomplete contracts; investment decision-making; public ownership; management and governance; Unvollständiger Vertrag; Investition; Investitionsrisiko; Eigentümerstruktur; Corporate Governance; Neuseeland